Genetic interaction mapping of Aurora protein kinases in mouse oocytes - Blengini, Cecilia S.; Schindler, Karen (Frontiers in Cell and Developmental Biology, 2024)
The Aurora Kinases (AURKs) are a family of serine-threonine protein kinases critical for cell division. Somatic cells express only AURKA and AURKB. However, mammalian germ cells and some cancer cells express all three isoforms. A major question in the field has been determining the molecular and cellular changes when cells express three instead of two aurora kinases. Using a systematic genetic approach involving different Aurora kinase oocyte-specific knockout combinations, we completed an oocyte-AURK genetic interaction map and show that one genomic copy of Aurka is necessary and sufficient to support female fertility and oocyte meiosis. We further confirm that AURKB and AURKC alone cannot compensate for AURKA.These results highlight the importance of AURKA in mouse oocytes, demonstrating that it is required for spindle formation and proper chromosome segregation. Surprisingly, a percentage of oocytes that lack AURKB can complete meiosis I, but the quality of those eggs is compromised, suggesting a role in AURKB to regulate spindle assembly checkpoint or control the cell cycle. Together with our previous studies, we wholly define the genetic interplay among the Aurora kinases and reinforce the importance of AURKA expression in oocyte meiosis.